DOI: 10.3990/1.9789036543217
|View full text |Cite
|
Sign up to set email alerts
|

Removal of engineered nanoparticles in drinking water treatment processes

Abstract: We passed through earth lightly as water, said Antonio Setzu, as water flowing, springs, from the dip full of the fountain, slides and winds among moss and ferns, down to the roots of the cork oak and almond trees or slips down on the stones, through the mountains and the hills up to the plan, from the streams to the river, slows down towards the swamps and the sea, called by the sun to become vapour and wind dominated cloud and blessed rain. Apart from the madness of killing each other for irrelevant reasons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 133 publications
0
6
1
Order By: Relevance
“…In addition, for both sizes, the uncharged NP showed a higher removal than the carboxylated NP. In contrast to current findings, an almost complete removal was determined experimentally for nano-silver (Gicheva and Yordanov 2013), and for nC60 fullerenes (Floris 2017). In full-scale DWTPs an almost complete removal of MP with a size of approximately 1 µm was found when applying GAC filtration (Pivokonsky et al 2018, Wang et al 2020.…”
Section: Colloidal Filtration Theorycontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition, for both sizes, the uncharged NP showed a higher removal than the carboxylated NP. In contrast to current findings, an almost complete removal was determined experimentally for nano-silver (Gicheva and Yordanov 2013), and for nC60 fullerenes (Floris 2017). In full-scale DWTPs an almost complete removal of MP with a size of approximately 1 µm was found when applying GAC filtration (Pivokonsky et al 2018, Wang et al 2020.…”
Section: Colloidal Filtration Theorycontrasting
confidence: 99%
“…Settling times of 10 minutes (Volk et al 2000) to 30 minutes (Floris 2017) seem to represent full-scale DWTPs the best. Using a syringe the supernatant (2 cm below the water surface)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the nanoplastics FeCl 3 concentrations of 12 and 18 mg FeCl 3 /L were applied which is similar to concentrations in full scale DWTPs 16,44,45 and to a previous investigation. 32 In pre-tests it was confirmed that these Fe concentrations sufficiently reduce the water turbidity (2100Q PorTable 6-Turbidimeter, HACH, US) and TOC (LCK380, HACH, US). After adding NPs to the surface water (10 mg L −1 , admixed for 30 minutes at 60 rpm) the actual CFS started.…”
Section: Chemicals and Methodsmentioning
confidence: 85%
“…The removal of nanoparticles by means of CSF has been described in literature, [32][33][34][35][36][37][38] but studies on sand or GAC (granular activated carbon) filtration are limited. Ramirez Arenas et al [39][40][41] studied the effect of coagulation and filtration over sand or GAC filters on the removal of polystyrene nanoparticles (90 ± 7 nm).…”
Section: Introductionmentioning
confidence: 99%